Pengembangan Media Pembelajaran Fisika Interaktif Berbasis Macromedia Flash 8 Materi Gerak Lurus - Agus Hardianto; Khaerus Syahidi; Tsamarul Hizbi; Fartina Fartina (Kappa Journal, 2020)
This study aims to produce interactive physics learning media based on macromedia flash 8 straight motion material for Class VII Students of SMP / MTs. This type of research uses the Research and Depelopment (R&D) approach by adopting the ADDIE (Analyze, Design, Depelopment, Implementation, and Evaluation) development model. Design the learning media trial using the Post-Test Only Control Group Design. Data collection instruments in the form of material expert evaluation questionnaire, media expert evaluation questionnaire, science subject teacher evaluation questionnaire, student response questionnaire, multiple choice tests and student learning activity questionnaire, data collection techniques namely test techniques and observation techniques. Data analysis techniques are media feasibility test, normality test, variance homogeneity test and hypothesis test. The results of the study of the feasibility aspects of instructional media, media experts declared worthy of an actual score of 75, material experts declared worthy of an actual score of 73, the subjects of Natural Sciences stated worthy of an actual score of 66, and the average score of actual responses of 4 students was 58.25 . While the results of research on the aspect of learning media testing showed that interactive physics learning media based on macromedia flash 8 was effective on student learning outcomes with an average experimental class score of 70.38 and classical learning completeness of 71.42%. The percentage of active students in the good category with a percentage of 69.09%. When compared with the control class with an average value of 50.37 and classical learning completeness 22.22%. The percentage of active students in the category is sufficient with a percentage of 41.82%.DOI : 10.29408/kpj.v4i1.2275